Impact of reanalysis of nitrogen multiple-breath washout on its relationship with chest magnetic resonance imaging findings in clinically stable and pulmonary exacerbated children with cystic fibrosis - Meißner, Maria; Steinke, Eva; Wielpütz, Mark Oliver; Joachim, Cornelia; Sommerburg, Olaf; Mall, Marcus A.; Stahl, Mirjam (Klinische Pädiatrie, 2024)
Rationale Multiple-breath washout (MBW)-derived lung clearance index (LCI) detects lung disease in children with cystic fibrosis (CF). Correction of a cross-talk error in the software of the MBW device Exhalyzer D in a new software version has generated significant interest regarding its impact on previous MBW findings. Since LCI and chest magnetic resonance imaging (MRI) correlated before in CF children, this study aims to reassess previous MBW data after correction.Patients/Methods Reanalysis of the main findings from a previously published study comparing MBW and MRI in a pediatric CF cohort by reassessment of nitrogen (N-2) MBW of 61 stable children with CF, 75 age-matched healthy controls (HC), and 15 CF children with pulmonary exacerbation (PEx) in the corrected software version.Results The corrected LCI (N2LCIcor) decreased in the entire cohort (-17.0 (11.2)%), HC (-8.5 (8.2)%), stable CF children (-22.2 (11.1)%), and within the PEx group at baseline, at PEx and after antibiotic therapy (-21.5 (7.3)%; -22.5 (6.1)%; -21.4 (6.6)%; all P<0.01). N2LCIcor and N2LCIpre correlated with chest MRI scores in stable CF (r=0.70 to 0.84; all P<0.01) without a significant difference between N2LCIcor and N 2 LCI pre . Change in LCI from baseline to PEx and from PEx to after therapy decreased from N 2 LCI pre to N2LCIcor, but these changes remained significant (all P=0.001).Discussion/Conclusions Our results indicate that N2LCIcor is significantly lower than N2LCIpre, but key results published in the original study demonstrating N2MBW and MRI as complementary methods for clinical surveillance in children with CF remain unaffected.